2001
DOI: 10.1007/bf03401836
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Macrophage Migration Inhibitory Factor as a Secretory Protein from Rat Epididymis: Evidences for Alternative Release and Transfer to Spermatozoa

Abstract: The cytokine MIF was identified in substantial amounts in the epithelial cells of rat epididymis and in the outer dense fibers of rat epididymal spermatozoa. Our results indicate a nonclassical secretion mode for MIF and suggest a cell-to-cell transfer of MIF via vesicles to the sperm cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
2
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 32 publications
3
44
2
3
Order By: Relevance
“…MIF, however, exists preformed in substantial amounts in the cytosol and nucleus of multiple cells, and its elaboration relies not only on de novo protein synthesis but on secretion from preformed stores (7,20,22,38,41). This is consistent with the present study, which identified constitutive MIF in whole cell cardiac Cardiac function values are expressed as means Ϯ SE.…”
Section: Discussionsupporting
confidence: 92%
“…MIF, however, exists preformed in substantial amounts in the cytosol and nucleus of multiple cells, and its elaboration relies not only on de novo protein synthesis but on secretion from preformed stores (7,20,22,38,41). This is consistent with the present study, which identified constitutive MIF in whole cell cardiac Cardiac function values are expressed as means Ϯ SE.…”
Section: Discussionsupporting
confidence: 92%
“…This secretory process is defined by protrusions or bleb emissions from the apical cytoplasm of the epithelium that form vesicular structures called exosomes, aposomes, or epididymosomes circulating in the lumen of the genital tract (Aumuller and Seitz, 1990). Some epididymosomeassociated proteins, such as CD52, glutathione peroxidase type 5, ubiquity, and macrophage migration inhibitory factor (MIF), are selectively transferred to spermatozoa during epididymal transit (Eickhoff et al, 2001;Sullivan et al, 2005). Hence, epididymosomes, which are characterized by their surrounding plasma membrane, are thought to be involved in the modification of spermatozoa during epididymal transit.…”
Section: Discussionmentioning
confidence: 99%
“…Studying the epithelium of rat epididymis, the principal cells have been delineated as the source of the cytokine, whereas the basal cells as well as the stromal cells were MIF negative [Eickhoff et al, 2001]. In addition, a differential distribution pattern with highest amounts of MIF in the caput region decreasing in more distal parts of the epididymis was described in that report, and MIF was also localized in vesicles detectable in the epididymal fl uid [Eickhoff et al, 2001].…”
mentioning
confidence: 91%